THE ROLE OF THE MATERIALITY IN AUDIT AND ACCOUNTACY IN AGRICULTURAL ORGANIZATIONS - BUMBESCU, Sorina Simona; OFILEANU, Dimi; BURDEA, Raul (Annales Universitatis Apulensis Series Oeconomica, 2014)
In this article it is realised an overview of the importance that the materiality has for the audit and the accountancy activity, beeing an interdependence relationship between the information provided by the accountancy and audit activity. Based on previous studies concerning the materiality, in this article it is developed a synthetic theoretical framework regarding the materiality, the relationship between materiality and audit risk, the steps that heve to be made in order to determine the materiality, and ultimately it is realised a case study concerning the calculation and analysis of the materiality in an agriculture entity. The research leads to two major categories of tangible results; on the one hand it is realised a qualitative theoretical synthesis on materiality, on the other hand, it exemplifies the calculation and analysis of materiality, and last but not least it highlights the importance of determining the materiality for the activity of any organization.